2010
DOI: 10.1104/pp.110.167841
|View full text |Cite
|
Sign up to set email alerts
|

A Domain-Centric Analysis of Oomycete Plant Pathogen Genomes Reveals Unique Protein Organization    

Abstract: Oomycetes comprise a diverse group of organisms that morphologically resemble fungi but belong to the stramenopile lineage within the supergroup of chromalveolates. Recent studies have shown that plant pathogenic oomycetes have expanded gene families that are possibly linked to their pathogenic lifestyle. We analyzed the protein domain organization of 67 eukaryotic species including four oomycete and five fungal plant pathogens. We detected 246 expanded domains in fungal and oomycete plant pathogens. The analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 73 publications
(89 reference statements)
3
74
0
2
Order By: Relevance
“…Table 4 shows that the relative number of apoplastic effectors identified in the P. viticola secretome is very similar to that predicted in the H. arabidopsidis genome [10]. The most prevalent domains identified were proteins containing glycosyl hydrolase and protease domains ( Table 4) in agreement with previous studies that have shown these two classes of highly abundant enzymes to be linked to pathogenicity in oomycetes [8,65].…”
Section: Apoplastic Effectors Secreted By P Viticolasupporting
confidence: 85%
“…Table 4 shows that the relative number of apoplastic effectors identified in the P. viticola secretome is very similar to that predicted in the H. arabidopsidis genome [10]. The most prevalent domains identified were proteins containing glycosyl hydrolase and protease domains ( Table 4) in agreement with previous studies that have shown these two classes of highly abundant enzymes to be linked to pathogenicity in oomycetes [8,65].…”
Section: Apoplastic Effectors Secreted By P Viticolasupporting
confidence: 85%
“…Several plant-infecting oomycetes have large expansions of NLPs in their genomes (25)(26)(27), suggesting that these proteins play an important role in the pathogen's lifestyle. A clear virulence function was observed for NLP Pcc of the rot bacterium Pectobacterium carotovorum (27).…”
Section: Significancementioning
confidence: 99%
“…We could also identify five out of the seven berberine-like proteins encoded in the genome. These proteins that are involved in alkaloid biosynthesis and in the production of hydrogen peroxide through the oxidation of numerous metabolites (63), and they are thought to be important virulence factors induced during plant infection (17,64). Alternatively, these proteins might also protect Phytophthora from plant counter defenses.…”
Section: Figmentioning
confidence: 99%